Dynamics of a Stage Structured Pest Control Model in a Polluted Environment with Pulse Pollution Input. (26th October 2013) - Liu, Bing; Xu, Ling; Kang, Baolin
Abstract : By using pollution model and impulsive delay differential equation, we formulate a pest control model with stage structure for natural enemy in a polluted environment by introducing a constant periodic pollutant input and killing pest at different fixed moments and investigate the dynamics of such a system. We assume only that the natural enemies are affected by pollution, and we choose the method to kill the pest without harming natural enemies. Sufficient conditions for global attractivity of the natural enemy-extinction periodic solution and permanence of the system are obtained. Numerical simulations are presented to confirm our theoretical results.